Changing Dimensions of Biodiversity Conservation with Stakeholders Participation in India - Path Ahead - Mishra, B. K.; Badola, Ruchi; Bhardwaj, A. K. (Indian Forester, 2010)
Creation and subsequent expansion of Protected Area (PA) network has often deprived local people of their usufruct rights and displaced communities from their traditional lands. This ’isolationist’ approach has resulted in severe conflicts between local people and PA authorities. Poverty and lack of alternative livelihoods for forest based communities, along with inability to mainstream biodiversity concerns in development planning around biodiversity-rich areas have been recognized as some of the root cause of threats to biodiversity conservation, and this sowed the seed of an alternate precept and practice of conservation which eventually came to be known as ’ecodevelopment’. This approach lays emphasis on community participation, explicitly recognizes the special needs of disprivileged and poorest of poor populations within local communities, and attempts to take care of their needs in the programme design. The process of ecodevelopment as evolved in and around PAs of India, has been a step by step action for it and had to deal with the biophysical complexities and socio-political dimensions of biodiversity conservation. This paper attempts to highlight the lessons learnt, critical factors that have contributed to the success of these initiatives, and the range of complex issues that have emerged while implementing ecodevelopment projects in India. It also provides an opportunity of exploring the possibility of expanding this program beyond the boundaries of the PAs.